An Automated, Self-Powered, and Integrated Analytical Platform for On-Line and In Situ Air Quality Monitoring - da Silva Sousa, Danielle; Leal, Vanderli Garcia; dos Reis, Gustavo Trindade; da Silva, Sidnei Gonçalves; Cardoso, Arnaldo Alves [UNESP]; da Silveira Petruci, João Flávio (MDPI, 2022)
Air quality monitoring networks are challenging to implement due to the bulkiness and high prices of the standard instruments and the low accuracy of most of the described low-cost approaches. This paper presents a low-cost, automated, self-powered analytical platform to determine the hourly levels of O3 and NO2 in urban atmospheres. Atmospheric air was sampled at a constant airflow of 100 mL min−1 directly into vials containing 800 µL of indigotris sulfonate and the Griess–Saltzman reagent solutions for ozone and nitrogen dioxide, respectively. The analysis holder, containing a light-emitting diode and a digital light sensor, enabled the acquisition of the analytical signal on-site and immediately after the sampling time. The data were transmitted to a laptop via Bluetooth, rendering remote hourly monitoring. The platform was automated using two Arduino Uno boards and fed with a portable battery recharged with a solar panel. The method provided a limit of detection of 5 and 1 ppbv for O3 and NO2, respectively, which is below the maximum limit established by worldwide regulatory agencies. The platform was employed to determine the levels of both pollutants in the atmosphere of two Brazilian cities, in which one of them was equipped with an official air quality monitoring station. Comparing the results of both techniques revealed suitable accuracy for the proposed analytical platform. Information technology (IT) allied to reliable chemical methods demonstrated high potential to create air quality monitoring networks providing valuable information on pollutants’ emissions and ensuring safety to the population.
Keywords: air pollution monitoring; air quality; nitrogen dioxide; ozone; remote gas sensing